INTEGRATION SOCIALE DES PEUPLES AUTOCTHONES PYGMEES A MBANDAKA EN REPUBLIQUE DEMOCRATIQUE DU CONGO : PROBLEMES ET PERSPECTIVES - BAYONGO N’KOMBE, Jean- Louis EOMA (IJRDO - Journal of Social Science and Humanities Research, 2021)
Less educated, non property owners and forest, complexed owing all Bantu, without arguments, the Pygmy copes today to the fast destruction of the ecosystems that represented their whole life: natural habitation, place of cults to the forebears, pharmacy, store of provision in products of first necessity. Being obliged to escape these surroundings because of the endogenous and exogenous factors that exhaust the vital resources, the Pygmy are forced to a migration in city. They meet in city where they have difficulties of integration. To survive in this new middle, the Pygmy exercise carter's profession, docker, sentry and domestic